2007
DOI: 10.1111/j.1365-2788.2007.00950.x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of antipsychotic medication in the management of behaviour problems in adults with intellectual disabilities

Abstract: Presently, there is RCT-based evidence for risperidone to be effective in both adults and children; however, this treatment carries a certain amount of risk associated with adverse effects. There is also evidence to support the use of other antipsychotics, primarily atypicals, but the evidence is based on noncontrolled case studies. There is currently not enough evidence available to recommend specific medication for specific behaviour problems. Before prescribing medication, clinicians should carry out a thor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 16 publications
0
49
0
1
Order By: Relevance
“…First, it is remarkable how few RCTs of psychotropics for common psychiatric disorders, such as depression, anxiety, and schizophrenia, in people with DDs have been published. For example, the systematic reviews of Deb's group [71][72][73][74][75] occasionally allude to this issue, but did not report any data that directly addressed it. This may reflect the problems of making psychiatric diagnoses that are sufficiently reliable for drug trials; however, at least 1 study 82 showed that psychiatrists with experience with ID diagnosed depression during the last 2 years and presence of hallucination and delusions during the last 12 months in people with mild and moderate IDs, with kappas of about 0.7, but with kappas dropping to about 0.5 for psychosis in people with moderate IDs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, it is remarkable how few RCTs of psychotropics for common psychiatric disorders, such as depression, anxiety, and schizophrenia, in people with DDs have been published. For example, the systematic reviews of Deb's group [71][72][73][74][75] occasionally allude to this issue, but did not report any data that directly addressed it. This may reflect the problems of making psychiatric diagnoses that are sufficiently reliable for drug trials; however, at least 1 study 82 showed that psychiatrists with experience with ID diagnosed depression during the last 2 years and presence of hallucination and delusions during the last 12 months in people with mild and moderate IDs, with kappas of about 0.7, but with kappas dropping to about 0.5 for psychosis in people with moderate IDs.…”
Section: Discussionmentioning
confidence: 99%
“…Their review of mood stabilizers 74 identified only one RCT of lithium. 80 This series of systematic reviews [71][72][73][74][75] of psychotropics for people with ID are probably the best available at this time; they are notable for their explicit reporting of methodology and careful reporting of what information is currently available on side effects, but reflect the limited quantity of information currently available and the often poor quality of the RCTs. Two limitations of this project were that Deb's group did not conduct meta-analyses and report ESs, NNTs, and numbers needed to harm, and the reviews are now dated and may not reflect developments during the last 5 years.…”
Section: Intellectual Disabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacotherapy is a common strategy, but there is only limited empirical support for its effectiveness (Deb et al 2007;Matson and Neal 2009;Tyrer et al 2008). Given the limited efficacy and purported side effects of psychotropic drugs for the treatment of individuals with intellectual disabilities, there has been a call to refrain from using antipsychotic drugs for treating maladaptive behaviors, such physical aggression, in this population (Tyrer et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The necessary or effective use of medication in regard to people with intellectual disability is debated with reports of up to 45% of people with intellectual disability receiving psychotropic medication and up to 30% of that group receiving it to manage behavioural problems only (Deb, Sohanpal, Soni, Lenotre, & Unwin, 2007;.…”
Section: Discussionmentioning
confidence: 99%